PHP 8 Revealed - Use Attributes, the JIT Compiler, Union Types, and More for Web Development - Engebreth, Gunnard (Apress, an imprint of Springer Nature, 2021)
Discover the new and updated features of PHP 8, such as the JIT compiler, union types, and attributes, with code examples of each. For each feature, the author includes real-life cases for its use and explains its benefits.